2009
DOI: 10.1029/2008wr007031
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Kalman filter data assimilation for a process‐based catchment scale model of surface and subsurface flow

Abstract: [1] A sequential data assimilation procedure based on the ensemble Kalman filter (EnKF) is introduced and tested for a process-based numerical model of coupled surface and subsurface flow. The model is based on the three-dimensional Richards equation for variably saturated porous media and a diffusion wave approximation for overland and channel flow. A one-dimensional soil column experiment and a three-dimensional tilted v-catchment test case are presented. A preliminary analysis of the assimilation scheme is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 44 publications
4
102
0
Order By: Relevance
“…This indicates that the unrealistic inter-variable and cross-variable correlations may exist in the model ensemble. In a similar study, Camporese et al (2009b) showed the EnKF assimilation of surface soil moisture can actually improve the saturated zone and assimilation of groundwater head can also improve surface soil moisture, where the saturated and unsaturated zones are based on solving the 3-D Richards equation for the entire subsurface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the unrealistic inter-variable and cross-variable correlations may exist in the model ensemble. In a similar study, Camporese et al (2009b) showed the EnKF assimilation of surface soil moisture can actually improve the saturated zone and assimilation of groundwater head can also improve surface soil moisture, where the saturated and unsaturated zones are based on solving the 3-D Richards equation for the entire subsurface.…”
Section: Discussionmentioning
confidence: 99%
“…Xie andment Tool (SWAT), with updating of multiple states and parameters including runoff, soil moisture and evapotranspiration. Camporese et al (2009b) used EnKF in the CATHY (CATchment HYdrology) model with coupled surface and subsurface flow, to assimilate groundwater head and stream discharge. Rasmussen et al (2015) assimilated the same variables using the ensemble transform Kalman filter (ETKF) with the MIKE SHE model.…”
Section: Introductionmentioning
confidence: 99%
“…With this method, the water table simulated by the saturated zone is consistent with the soil moisture profile. This class of methods can dynamically describe return flow, regional groundwater circulation, groundwater discharge, and saturation excess runoff [see also Camporese et al, 2009;Camporese et al, 2010].…”
mentioning
confidence: 99%
“…Moreover, it is still not clear how the ensemble size should scale with the system dimension to achieve adequate estimates (Reichle et al, 2002a;Camporese et al, 2009). In case of linear systems, the solution of EnKF converges to that of SKF as the ensemble size increases (Evensen, 2003).…”
Section: Ensemble Kalman Filter (Enkf)mentioning
confidence: 99%
“…It has become a popular choice for data assimilation in traditional hydrological applications like the estimation of streamflow (Moradkhani et al, 2005;Clark et al, 2008;Weerts and El Serafy, 2006;Xie and Zhang, 2010), land surface energy fluxes (Dunne and Entekhabi, 2006;Pipunic et al, 2008) and soil moisture (Reichle and Koster, 2003;Reichle et al, 2007;De Lannoy et al, 2007). It has also been applied in subsurface models based on the numerical solver of the Richards equation (Das and Mohanty, 2006;Huang et al, 2007;Camporese et al, 2009).…”
Section: Introductionmentioning
confidence: 99%